Systematic Cost Framework by Application of Universal Design (UD) Concept for Operating Instructions in Design Stage - Alauddin, Nursuhana; Shuib, Solehuddin (International Journal of Engineering and Technology, 2018)
This paper is based on the new product development (NPD) flow and environment of the writerâ€™s organization. The consideration to minimize cost in NPD requires a lot of efforts to tolerate with challenges and uncertainties throughout the process. If cost is not analyzed and monitored in the early stage of NPD, it may not be able to reduce remarkably as a total product. One of the components to complement main body is the operating instructions (OI). Currently, when conducting cost analysis of OI during design stage, the cost is not systematically calculated due to the tendency to maintain cost with previous model. Furthermore, product liability (PL) consideration in OI is mandatory and it is a challenge to balance up this concept with cost reduction. This research aimed to develop a systematic way of cost framework by applying the universal design (UD) concept for OI. The result has shown the achievement of OI cost reduction in artwork development (expenses) and direct material cost during component designing stage in NPD. It is hoped that the study may contribute to manage OI cost in more systematic way and to provide understanding to design the OI with UD mindset in NPD.Â Â